Social return on investment for community-based alcohol consumption control program during Buddhist Lent - Varangkanar Jirarattanasopha; Nopphol Witvorapong; Piya Hanvoravongchai (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to evaluate the cost and benefit of a community-based alcohol consumption control program during the Buddhist Lent (BL) period in terms of social return on investment (SROI). Design/methodology/approach - The research team evaluated the program in four selected villages from four regions using standard SROI. Relevant stakeholders were involved in the evaluation design and program impact map construction. Data, including costs, were collected from literatures, official documents, stakeholder interviews and focus group discussions. Alcohol abstinence and related data during and after the 2015 BL period were gathered from a survey questionnaire. The SROI ratio presented the social benefits compared against the total social investment. Findings - The program was effective in producing a greater social value (2.7-5.9 times) than the cost of investment in every village. Cost savings from alcohol consumption constituted a major proportion of the program's value. Originality/value - The community-based alcohol consumption control program during BL can provide value for investment. Information from this study can be used by policy makers in their decision to continue or scale up the program. The SROI approach mainly relies on stakeholders that may present a bias; however, further study such as social cost-benefit analysis could provide additional insights.